PENGARUH KUALITAS PELAYANAN, FASILITAS DAN KINERJA MEDIS & NON MEDIS TERHADAP KEPUASAN PASIEN RAWAT INAP RUMAH SAKIT UMUM ISLAM BANYU BENING BOYOLALI - Suraningtyas Widyastuti; Anggit Dyah Kusumastuti; Annisa Indah Mutiasari (Bisnis-Net, 2023)
The study aims to determine the effect of service quality, facilities, and medical & non-medical performance on patient satisfaction at Banyu Bening Boyolali Islamic General Hospital. The research method used a quantitative descriptive. The population was all third class inpatients from January to March 2023. The sampling technique used the Slovin formula so that a total sample of 336 respondents was obtained. The results show that the variables of service quality and medical & non-medical performance affected patient satisfaction. Meanwhile the facility variable does not affect patient satisfaction. The most dominant variable in this study is medical & non-medical performance rather than the quality of services and facilities. The Adjusted R square value is 46.7%. The patient satisfaction variable can be explained by the variables of service quality, facilities, and medical & non-medical performance. Meanwhile, the remaining 53.3% is explained by other variables not discussed in this study.Keywords: service quality, facilities, medical & non-medical performance, patient satisfaction.